2009
DOI: 10.1016/j.jacc.2009.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Global 2-Dimensional Strain as a New Prognosticator in Patients With Heart Failure

Abstract: GCS is a powerful predictor of cardiac events and appears to be a better parameter than ejection fraction in patients with acute heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
274
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(301 citation statements)
references
References 22 publications
16
274
1
10
Order By: Relevance
“…In 201 patients with heart failure (number of patients with CKD not stated), Cho et al reported that global circumferential strain is an independent and better predictor of cardiac events (readmission for heart failure or cardiac death) than left ventricular ejection fraction. 52 Several studies described a reduction of left ventricular strain parameters in patients with CKD or ESRD despite preserved left ventricular ejection fraction. [53][54][55] Edwards et al reported that patients with early-stage CKD (CKD stages 2-3) have impaired systolic strain and strain rate values (assessed by Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…In 201 patients with heart failure (number of patients with CKD not stated), Cho et al reported that global circumferential strain is an independent and better predictor of cardiac events (readmission for heart failure or cardiac death) than left ventricular ejection fraction. 52 Several studies described a reduction of left ventricular strain parameters in patients with CKD or ESRD despite preserved left ventricular ejection fraction. [53][54][55] Edwards et al reported that patients with early-stage CKD (CKD stages 2-3) have impaired systolic strain and strain rate values (assessed by Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies of LV strain and outcomes in community‐dwelling individuals free of overt CVD 10, 11. Furthermore, the degree to which distinct components of LV deformation in various planes provide specific prognostic information regarding risk of individual CVD outcomes (eg, coronary disease vs. HF) remains unclear 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that global circumferential strain (GCS) assessed by 2D speckle-tracking strain in the mid-LV short-axis view reflects LV intrinsic myocardial function, 18, 19 and constitutes an independent prognostic marker for the prediction of cardiovascular events regardless of markers of LV global function such as ejection fraction (EF) in HF patients. 19 Accordingly, our objective was to test the hypothesis that an easy-to-use comprehensive speckle-tracking approach that combined assessment of LV radial dyssynchrony and GCS ardiac resynchronization therapy (CRT) is an established therapeutic option for advanced heart failure (HF) patients with severe symptoms and wide QRS duration.…”
mentioning
confidence: 99%